Invivo gastric antiulcer activity of syringin (phenyl propanoid glucoside) studied in different ulcer induced experimental rat models - U.S. Mahadeva, Rao; C., Shanmuga Sundaram (Scholars Research Library, 2016)
Most of the currently available oral antiulcer drugs for the treatment of peptic ulcer provoke detrimental adversative effects. Hence, the exploration for plant-derived products for the treatment of ulcer continues. Syringin, a phenylpropanoid glucoside found in the tepals of Musa Paradisiaca, has many biological properties, including as an antioxidant, immunomodulatory and antidiabetic agent. The preventive and curative effects of syringin for ulcers were evaluated using models of acute gastric lesions induced by ethanol and indomethacin in rats. Moreover, the effects of ethanolic extract of syringin on gastric content volume, total acidity and pH, using the pylorus ligated model were also evaluated. Animals pretreated with syringin extract showed a significant reduction in lesion index in both ethanol and indomethacin induced ulcer models in a dose dependent manner when compared to the control group. Similarly, post-treatment with syringin (50 mg/kg body weight) for a period of 15 days revealed a statistically significant improvement in the ulcer healing process (p <0.05). In the pylorus ligated model, it was observed that the syringin displayed an antisecretory activity, which led to a significant reduction in the gastric juice volume, total acidity and pH. These findings indicate that syringin displays both ulcer preventive and ulcer curative properties and provides a scientific rationale for the use of syringin in the traditional medicinal system.